PERAN PEMODERASI KUALITAS AUDIT ATAS PENGARUH PERENCANAAN PAJAK DAN PAJAK TANGGUHAN TERHADAP MANAJEMEN LABA - Sitompul, Renato; Reskino, Reskino (CURRENT: Jurnal Kajian Akuntansi dan Bisnis Terkini, 2021)
The purpose of this study is to examine the impact of tax planning and deferred tax assets on earnings management in manufacturing companies listed on the Indonesia Stock Exchange from 2016 to 2018. An explanatory strategy with a quantitative approach is used in this study design. Secondary data sources used in this study include the company's financial statements on the balance sheet, profit and loss, and cash flow. This study used a sample of 73 manufacturing companies that were listed on the Indonesia Stock Exchange between 2014 and 2016. Univariate and moderated regression analysis models were used to analyze the data. The findings of this study show that tax planning has a favorable impact on earnings management and audit quality, with KAP Big 4 enterprises performing lower earnings management than KAP non-Big 4 firms. . Furthermore, deferred tax does not increase the favorable impact on earnings management, and firms audited by KAP Big 4 in deferred tax have lower earnings management than firms audited by KAP non-Big 4.